Low-carbon, hydrogen-rich syngas from sorption-enhanced gasification: A review - Dziva, Godknows; Weitzel, Jonas; Cui, Pengjun; Yew, Maxine; Ding, Guangchao; Zeng, Liang; Li, Songgeng (Carbon Capture Science & Technology, 2025)
•Sustainable energy conversion via sorption-enhanced gasification is thoroughly reviewed.•Fundamental reactions and limitations of CaO sorbents are critically examined.•Pilot-scale tests are analyzed to highlight advancements and gaps in SEG research.•Practical challenges and process intensification strategies are discussed. This review aims to provide a comprehensive overview of sorption-enhanced gasification (SEG) with CaO, highlighting its potential as an efficient and sustainable energy conversion technology. SEG integrates dual bed steam gasification with in situ CO2 removal using CaO, efficiently converting solid carbonaceous fuels such as biomass and low-rank coal into hydrogen-rich (up to 80 vol% H2), low-carbon and tar, medium calorific value and nitrogen-free syngas that can be adapted for various downstream applications. The review details the working principle, operating conditions and reaction mechanisms of SEG, emphasizing how these factors influence product distribution. Calcium sorbents are central to the SEG process, so their reactions, catalytic activity and limitations are discussed in this review. Pilot-scale tests are examined to underscore process engineering advancements as well as to highlight scale-up challenges that currently limit the technology to TRL 5–6. Unsustainable long-term sorbent performance and energy penalties from sorbent regeneration and CO2 capture still need to be addressed through scalable and cost-effective material development and process engineering. This review discusses various process intensification concepts as potential solutions to the inherent shortcomings of SEG. Process systems analyses examined indicate the potential of SEG in hydrogen, synthetic fuel and electricity production, positioning it as a promising technology for decentralized sustainable energy conversion. Furthermore, the review explores the sustainable repurposing and disposal of spent solids to foster circular economies. Overall, this comprehensive review provides crucial insights to further leverage and advance the SEG process, offering a platform for future research and development. [Display omitted]